Fatty fish intake in mothers during pregnancy and in their children in relation to the development of obesity and overweight in childhood: The prospective ABIS study - Karel Duchen; Åshild Olsen Faresjö; Sofia Klingberg; Tomas Faresjö; Johnny Ludvigsson (Wiley, 2020)
Summary Background Although controversial, lower maternal intake of n‐3 polyunsaturated fatty acid (PUFA) during pregnancy and lower levels of omega‐3 PUFA in serum phospholipids during childhood have been related to obesity. The main source of omega‐3 PUFA is fatty fish in the diet. Objectives To assess the relationship between overweight/obesity and the intake of fatty fish in maternal diet during pregnancy and in children up to 8 years of age. Methods The prospective cohort All Children in South‐East Sweden (ABIS) followed babies from birth to 8 years of age. A total of 6749 children at 5 years of age (boys 52.6%) and 3017 children at 8 years (boys 52.3%) participated. A "fatty‐fish index" was constructed on the basis of self‐reports of nutritional habits. Results The prevalence of overweight and obesity in children at 5 years were 12.9% and 4.2%, respectively. At 8 years, 12.2% of the children presented overweight and 2.3% obesity. Girls were more affected than boys by overweight/obesity. A higher fish index during pregnancy was not related to overweight/obesity in the children, whereas a higher fish index in the children during the first years of life was related to obesity at 5 and 8 years of age. This relationship disappeared in a multivariable analysis. Maternal body mass index (BMI), maternal education, maternal smoking during pregnancy, birth weight, and physical activity all remained related to overweight/obesity at both 5 and 8 years of age. Conclusion No relationships were found between a lower intake of fatty fish in the diet, neither in mothers during pregnancy nor in early childhood, and increased risk of overweight/obesity.